Current treatment of difficult airway: a practical review of advanced techniques for airway management - Mendoza-Aceves, Rodrigo A.; Ortega Madrid, Enrique; Meade Yovanovich, Karen; Bernal Barroeta, Brenda; Gómez-Mendoza, Francisco Fabián; Banegas-Ruiz, Rodrigo; Barrera-Mera, Baltazar; Valderrama-Treviño, Alan I. (International Journal of Research in Medical Sciences, 2021)
The airway by definition is a conduit through which the air passes; or it is the route by which the air travels from the nose or mouth to the lungs. An exhaustive review was performed with the available literature using the PubMed, ScienceDirect, Scopus and Cochrane databases from 2009 to 2021. The search criteria were formulated to identify reports related to difficult airway management. To allow controlled ventilation, the airway must meet two characteristics in priority order, be permeable and airtight. In assessing risk, in addition to looking for predictors of difficult airway, it was important to understand the global clinical circumstances. Faced with a patient with a difficult airway, decision-making must be agile and correct since any decision can modify the clinical outcome.